PERANCANGAN ANIMASI 3 DIMENSI ISLAM DENGAN MENERAPKAN METODE POSE TO POSE “DUO DURO : SABAR” - Raditya, Rifqi Azhar; Agustin, Nanda Bintang; Roynaldi, Kholid; Aziz, Sulthon Abdul; Munawaroh, Siti; Zahrah, Yusminnu (Pusat Penerbitan LPPM ISI Bali, 2025)
The integration of digital technology in education is crucial to prepare the younger generation for Industry 4.0, emphasizing on technological skills and moral values. However, challenges such as inadequate IT skills among educators and inadequate infrastructure hinder the effective use of technology in learning. This research advocates the use of multimedia, particularly 3D animation, to enhance student engagement and their understanding of complex concepts. Blender, an open-source 3D authoring tool, is highlighted for its flexibility and cost-effectiveness in producing high-quality animations. This article presents a case study of an Islamic-themed animation,